2012
DOI: 10.1093/infdis/jis675
|View full text |Cite
|
Sign up to set email alerts
|

Defining Falciparum-Malaria-Attributable Severe Febrile Illness in Moderate-to-High Transmission Settings on the Basis of Plasma PfHRP2 Concentration

Abstract: Background. In malaria-endemic settings, asymptomatic parasitemia complicates the diagnosis of malaria. Histidine-rich protein 2 (HRP2) is produced by Plasmodium falciparum, and its plasma concentration reflects the total body parasite burden. We aimed to define the malaria-attributable fraction of severe febrile illness, using the distributions of plasma P. falciparum HRP2 (PfHRP2) concentrations from parasitemic children with different clinical presentations.Methods. Plasma samples were collected from and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 45 publications
7
94
1
Order By: Relevance
“…Thus, the quantitative H-VNB diagnostics of malaria will require additional calibration. Parasitemia level as currently measured also does not always correlate with disease severity (22,23). Therefore, after a detailed preclinical study, the H-VNBs may reveal unique diagnostic and prognostic metrics.…”
Section: Significancementioning
confidence: 96%
“…Thus, the quantitative H-VNB diagnostics of malaria will require additional calibration. Parasitemia level as currently measured also does not always correlate with disease severity (22,23). Therefore, after a detailed preclinical study, the H-VNBs may reveal unique diagnostic and prognostic metrics.…”
Section: Significancementioning
confidence: 96%
“…Thus, restoration of EPCR functions may be a key target for adjunctive malaria drug treatments. protein 2 (PfHRP2), a surrogate of parasite biomass, can predict disease severity and fatality rates in both children and adults (31,32), the probability of disease deterioration (33), retinopathy-positive cerebral malaria (34), and whether a fever is caused by malaria (35). Nevertheless, a recent longitudinal study in Tanzanian children showed that high PfHRP2 levels did not necessitate severe disease (36), suggesting severe disease requires additional factors.…”
Section: Significancementioning
confidence: 99%
“…Levels of PfHRP-2 in plasma most often do not correlate with parasitemia. 23,24 Here, we identified PfHRP-2 by both an RDT using a minimum volume of 10 μL and by immuno-PCR using an average volume of 5 μL because of limited volume in archival samples. The non-repetitive protein aldolase was mostly absent from CSF by RDT, either from lack of sensitivity of the RDT for aldolase compared with PfHRP-2 in CSF (as is described in whole blood) 25 or because proteolysis between capture and detection epitopes for the RDT makes aldolase in CSF not detectable in the RDT format.…”
Section: Discussionmentioning
confidence: 99%
“…The PfHRP2 levels in uncomplicated malaria are about 100 to 300 ng/mL. 17,24,27 The PfHRP-2 could enter the CSF by the choroid plexus with its fenestrated endothelium and specialized epitheloid cells that generate a 200-fold reduction in protein as they produce CSF from plasma. 26 Additionally, 50% of CSF is made from interstitial fluid in brain parenchyma, which drains directly into ventricles.…”
Section: Discussionmentioning
confidence: 99%